Investiga Tion of the Sub-Cultivation and Maintenance Conditions of Spodoptera Frugiperda Cell Lines - Sh.B. Kadirova; D.B. Turdaliyev; R.B. Sayidova; J.Ch. Mengturayev; H.Sh. Ashuraliyev; A.H. Mardonov (American Journal of Biodiversity, 2025)
The current study analyzed growth, survival and regenerative potential of Spodoptera frugiperda (Sf9) insect cells in vitro. The growth kinetics of Sf9 cells were carried out in SF-900 II medium and allowed to grow at 26-27°C and further analyses included cell density, viability and cell count. After 96 hours, a density of 4.8 x 106 cells/ml was reached with respect to cell growth. Within the cryopreservation experiments, a b viability of 95% was achieved with the use of a medium containing 80% SF900 II, 10% DMSO, and 10% FBS after six months of storage. Moreover, a viral titer of 1.3x108 pfu/mL was obtained when the Sf9 cells were infected with Autographa californica multiple nucleopolyhedrovirus (AcMNPV). The results support the claim that Sf9 cells have high growth rate and high cryo-stress resistance, hence useful in the production of recombinant proteins and vaccines in Baculovirus Expression Vector Systems (BEVS). This is because of its high rate of growth, tolerance to crystal stress and the ability to replicate with viruses. In addition, these cells can also be used in the identification of viral pathogens like Human Papillomavirus (HPV) types and hepatitis B virus (HBV)